Implementation of Islamic Economic Principles in Strengthening the Community Economy Based on Msmes - An'im Fattach (Jurnal Multidisiplin Sahombu, 2026)
Islamic economics exists as an economic system that emphasizes the values of justice, balance, and welfare in economic activities. In the context of the national economy, Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth in society. This study aims to examine the implementation of Islamic economic principles in strengthening the MSME-based community economy. The research method used is a descriptive qualitative approach through literature study by analyzing Islamic economic books and relevant previous research results. The results of the study indicate that Islamic economic principles such as justice (al-'adl), honesty (shidq), responsibility (amanah), and mutual assistance (ta'awun) have been implemented in MSME practices, both in the production, distribution, and transaction processes. The implementation of these principles contributes positively to increasing trust, business sustainability, and strengthening the community economy in an inclusive manner. This research is expected to serve as a conceptual reference for the development of Islamic economic-based MSMEs in Indonesia.